Swach Bharat Abhiyan: insights from students of a central university - Shamshad, Tazeen; Shah, Mohammad S.; Khalique, Najam; Ansari, Mohammad A. (International Journal Of Community Medicine And Public Health, 2021)
Background: Sanitation has been identified as one of the important determinants of the health and hygiene since ages. Sanitation and hygiene are critical to health, survival and development. Hygiene causes a global health challenge especially in the developing world. Considering the importance of hygiene, a cleanliness drive has been started in India i.e., Swach Bharat Abhiyan (SBA). The study was conducted to assess knowledge, perception and practices regarding SBA and to know the perception between medical and non-medical students towards clean India. Method: A cross sectional study done for a period of 5 months. A self-explanatory semi-structured questionnaire were used in this study with close ended questions. Sample size was taken as 416. Results: 98.1% of students were aware of SBA. Only 20.9% were agreed over building infrastructure like public toilets etc. which can help to achieve clean India while all others were disagreed. 65.1% people said that there is no decrease of vector borne disease while 34.9% people said it is. The perception regarding disposal of solid waste is mainly in the community bins by the students. Conclusions: The current study reflects that majority of the population were aware of SBA and its objective and the amount spent in SBA and the students of central university had shown positive attitudes and perception towards it to make India clean. SBA could have been much more impactful if it was clubbed with issuance of certain ordinance